The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1128/mcb.01321-09
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Exonuclease 5 Is Essential for Mitochondrial Genome Maintenance

Abstract: Yeast exonuclease 5 is encoded by the YBR163w (DEM1) gene, and this gene has been renamed EXO5. It is distantly related to the Escherichia coli RecB exonuclease class. Exo5 is localized to the mitochondria, and EXO5 deletions or nuclease-defective EXO5 mutants invariably yield petites, amplifying either the ori3 or ori5 region of the mitochondrial genome. These petites remain unstable and undergo continuous rearrangement. The mitochondrial phenotype of exo5⌬ strains suggests an essential role for the enzyme in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…Comparison of reaction products with a reference RNA fragment of the same length as the one present in the chimeric RNA–DNA substrate, as well as to an RNA ladder, showed that the major final product contained two deoxyribonucleotides downstream of the RNA fragment (Figure 5B). A similar feature was observed for another PD-(D/E)XK nuclease EXO5 (48). The second substrate (DNA–RNA) seemed fully degraded because the DNA portion of the molecule that was labelled can be hydrolyzed; however, as Ddk1 has no RNase activity, we assume that the RNA portion remains, although not visible in the autoradiogram (Figure 5B).…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Comparison of reaction products with a reference RNA fragment of the same length as the one present in the chimeric RNA–DNA substrate, as well as to an RNA ladder, showed that the major final product contained two deoxyribonucleotides downstream of the RNA fragment (Figure 5B). A similar feature was observed for another PD-(D/E)XK nuclease EXO5 (48). The second substrate (DNA–RNA) seemed fully degraded because the DNA portion of the molecule that was labelled can be hydrolyzed; however, as Ddk1 has no RNase activity, we assume that the RNA portion remains, although not visible in the autoradiogram (Figure 5B).…”
Section: Resultssupporting
confidence: 79%
“…An ssDNA substrate was treated with Ddk1, and the migration of reaction products was compared with a DNA ladder. This revealed that the major final product is 2 nucleotides in length, which is the same as observed for yeast EXO5 (48) (Figure 6B).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…A 5= DNA exonuclease activity, defined by the EXO5 gene, has been recently identified in yeast mitochondria (132,133). EXO5 is essential for the maintenance of ϩ but not the ori-containing hypersuppressive Ϫ genomes.…”
Section: Exonucleasesmentioning
confidence: 99%